The eggshell: strength, structure and function - Solomon, S.E. (British poultry science, 2010)
In making a journey through the literature of the last 50 years one can easily highlight a sequence of seminal works-but the route has not been direct and to avoid the many profitable diversions and detours that have enriched and deepened our collective understanding of the subject of eggshell structure and function is to do the subject a serious disservice. This is a route march of science enabled by advances in technology.